The Crucifixion Scene as the Climax of Lukan Inclusivity - Wilson, Benjamin R. 1983- (2016)
Many interpreters have noted that Luke’s gospel emphasizes the inclusive parameters of Jesus’ ministry, as figures from a wide range of social locations are characterized positively as the surprising recipients of divine favour and models of a faithful perspective toward Jesus. The present article considers Luke’s passion narrative in light of this prominent Lukan theme, finding that Luke’s special interest in the universality of Jesus’ ministry reaches its climax at the cross. The article outlines the inclusive parameters of Jesus’ ministry throughout Luke’s gospel and then shows how this theme is developed through the characterization of a series of figures within the passion narrative.
Keywords: Bible -- Criticism, Narrative; Bible. Gospels; Bible. Luke; BIBLICAL figures; Crucifixion; Inclusivity; Jesus Christ; Jesus Christ -- Crucifixion; Luke 23; Passion Narrative